Development of Validated Stability Indicating Method for Estimation of Vandetanib and Characterization of its Degradants by LC-ESI-MS - Salode, Vikrant Liladhar; Game, Madhuri Deorao; Salode, Gouri Vikrant; Gadge, Sonali Suresh (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim: In the current study, stability indicating high performance liquid chromatography method (RP-HPLC) was developed and validated for the determination of Vandetanib, also its major degradants were identified and characterized by Liquid Chromatography- Tandem Mass spectrophotometric method (LC-ESI-MS). Methods and Materials: This method was developed on Nucleosil 100-5, C18 (250×4.6 mm, 5μm) column by using Methanol: Ammonium acetate buffer as Mobile phase in the ratio, 90:10 v/v, having flow rate of 1 ml/min. The estimation was carried out at 249 nm. Further Vandetanib was subjected to various stress condition like acidic, alkali, oxidative, thermal and photolytic degradation. The degradation pathways for major degradants were idenitifed. Results: The method was developed and validated for linearity, robustness, accuracy, precision, linear regression analysis data which indicates the good linear relationship, correlation coefficient was found 0.992 in the concentration range of 1-10 μg/ml. In the stress results, the degradation of drug in alkaline, as well as acidic medium showed significantly. The product degradation was characterized by the LC-MS technique. Conclusion: The developed method was found to be rapid, sensitive, accurate, precise, and robust for the analysis of Vandetanib by which routine analysis of drugs can be done.
Keywords: Mass Spectroscopy (MS); Vandetanib; High-Performance Liquid; Chromatography (HPLC); Validation; Stress degradation